2021
DOI: 10.1038/s41598-021-02076-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fNIRS signal components elicited by cognitive and hypercapnic stimuli

Abstract: Functional near infrared spectroscopy (fNIRS) measurements are confounded by signal components originating from multiple physiological causes, whose activities may vary temporally and spatially (across tissue layers, and regions of the cortex). Furthermore, the stimuli can induce evoked effects, which may lead to over or underestimation of the actual effect of interest. Here, we conducted a temporal, spectral, and spatial analysis of fNIRS signals collected during cognitive and hypercapnic stimuli to character… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 102 publications
(148 reference statements)
1
16
0
Order By: Relevance
“…On the other hand, respiratory fluctuations affect the cerebral blood volume and flow [ 38 ]. Therefore, it can be expected that alternation in RR is revealed in fNIRS, and in particular, in signals [ 26 ]. Our underlying assumption, which was inspired from PPG-based studies [ 25 ], was that fluctuations in the frequency of signal’s baseline wander can be related to RR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, respiratory fluctuations affect the cerebral blood volume and flow [ 38 ]. Therefore, it can be expected that alternation in RR is revealed in fNIRS, and in particular, in signals [ 26 ]. Our underlying assumption, which was inspired from PPG-based studies [ 25 ], was that fluctuations in the frequency of signal’s baseline wander can be related to RR.…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by the studies that estimated RR from the photoplethysmography (PPG) [ 25 ], our hypothesis is that the baseline wander of fNIRS also might be related to alternations in the respiration. On the other hand, it has been shown that respiration has a stronger influence on the than the signal [ 26 ]. Hence, the basis of our method is to (i) extract the troughs of the signal, (ii) synthesize the baseline wander using the cubic spline interpolation of the extracted troughs, and (iii) find the dominant frequency of the baseline wander to estimate RR.…”
Section: Introductionmentioning
confidence: 99%
“…Similar, effects on brain activity changes using individual characteristics have been reported by other researchers [ 7 , 27 , 55 , 58 , 60 62 , 64 67 ]. The improvement was especially observed for HbR measures, which has been shown to be a more sensitive measure of cognitive activity than HbO for this particular task [ 45 ]. Furthermore, inclusion of these individual differences has provided further insight into interaction between performance and mental effort changes during multitasking training.…”
Section: Discussionmentioning
confidence: 99%
“…The model investigating behavioral measures used a random intercept design, while the model investigating mean fNIRS measures used non-correlated random intercept and slope design. The random slope term (0 + Short | ID) when evaluating mean fNIRS measures was used to separate task-induced extracerebral activity from that related to cerebral activity, which was shown to be significant in another study using the same dataset [ 45 ]. Lastly, to investigate performance and mental effort simultaneously, Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Although the HR estimation from fNIRS measurements has been addressed in several studies, no research, except for our previous study [ 16 ], has yet investigated the possibility of RR estimation from fNIRS. Respiration is one of the main physiological interferences in fNIRS, manifesting in its spectrum (∼0.2 to 0.4 Hz) [ 17 , 18 ]. The reason for such contamination is twofold; changes of the blood flow within the body during inhaling and exhaling, and the influence of respiratory oscillations on cerebral blood volume and flow [ 19 ].…”
Section: Introductionmentioning
confidence: 99%